Kupowanie poparcia. Polityka gospodarcza jako środek stabilizacji sytuacji wewnętrznej w Polsce w pierwszych miesiącach rządów Edwarda Gierka - Dwilewicz, Łukasz (Pamięć i Sprawiedliwość, 2008)
The crisis in the government’s leadership, caused by the worker protests on the Baltic coast, peaked at the Seventh Plenum of the Central Committee of Polish United Workers Party (PZPR), on December 20, 1970, and was immediately followed by efforts to defuse the social situation with promises of higher wages and improved living conditions, as well as concrete decisions intended to lend credence to the declarations of the new First Secretary, Edward Gierek. The new party and government leaders had to contend with social discontent caused by price increases as well as the consequences of earlier actions and promises of the authorities in the areas of economic and social policy. While it is not stated directly in the available archival materials, taking into account the context – in which specific decisions were taken, it can be recognized that to a signifi cant degree they were meant to ensure the social tranquility requisite for the governing of the new authorities and forming the basis for their enduring legitimization in eyes of the public. Economic policy in Gierek’s time was from the outset to be characterized by a turn towards increasing consumption. Moves taken to stabilize the situation within the country can be divided into those enacted under pressure of the situation and affecting the entire country (freezing of food prices, cancelling of price increases while maintaining income related compensations – introduced by Władysław Gomułka’s team), decisions concerning potentially the most dangerous industrial branches and regions, solving temporary problems as well as main issues connected with the development of these branches and regions, as well as those elements of economic policy guaranteeing the continuous improvement of standards of living and stable – support for the governing team (changes to the annual plan, a new fi ve-year plan concept, investment decisions aiming to ensure a proper supply of consumer goods in the future, the abolishment of mandatory delivery quotas in agriculture). The majority of decisions from the fi rst and second groups were taken in the fi rst two months of 1971, those that followed were mainly tied to the implementation of long-term changes to economic policy in the succeeding months. Changes, including the search for sources of fi nancing and technology in western countries, took place with the strong support of the Soviet Union. The combined effect of the actions, designed to improve society’s material situation, was the increase in average nominal personal income of 14% in 1971, and a 5.7% increase in real personal income (the largest annual increase since the end of the 1950s). The success, mainly achieved by the purely discretionary means of economic policy, was also the cause of the neglect of deeper systemic – reforms, directly evidenced by the successive loss of importance of the work of the so-called Szydlak Commission in tandem with the improvement of the country’s economic situation.